Fragrances and PAHs in snow and seawater of Ny-Ålesund (Svalbard): Local and long-range contamination. (November 2018) - Vecchiato, Marco; Barbaro, Elena; Spolaor, Andrea; Burgay, Francois; Barbante, Carlo; Piazza, Rossano; Gambaro, Andrea
Abstract: Polar regions are fragile ecosystems threatened by both long-range pollution and local human contamination. In this context, the environmental distribution of the Personal Care Products (PCPs) represent a major knowledge gap. Following preliminary Antarctic studies, Fragrance Materials (FMs) were analyzed in the seawater and snow collected in the area of Ny-Ålesund, Svalbard, to investigate local and long-range contamination. Polycyclic Aromatic Hydrocarbons (PAHs), including Retene, were determined in parallel to help the identification of the governing processes. Concentrations of FMs up to 72 ng L −1 were detected in the surface snow near the settlement and at increasing distances, in relation to the prevailing winds. PAHs follow a similar scheme, with levels of Retene up to 1.8 μg L −1, likely deriving from the occurrence of this compound in the coal dust due to the previous mining activities in the area. The snow seasonal deposition of FMs and PAHs was estimated in a snowpit dug at the top of the Austre Brøggerbreen glacier, indicating the long-range atmospheric transport (LRAT) of these compounds. Graphical abstract: Image 1 Highlights: First study on Fragrances in snow from Svalbard. Local and Long-Range Atmospheric Transport of FMs and PAHs. Salicylates result the most abundant FMs. High levels of Retene from coal dust. Abstract : Fragrances and PAHs in the area of Ny-Ålesund (Svalbard) derive from both local contamination and atmospheric transport.